Faktor Yang Mempengaruhi Kecemasan Perawat Pada Masa Pandemi Covid-19 Di Instalasi Rawat Inap RSUD Kota Makassar Tahun 2020 - Besse Nurul Kafilawaty; Asmawati Ahmad (Universitas Muhammadiyah Manado, 2021)
The impact of the Covid-19 pandemic has caused many losses, such as physical health problems, economic disparities, social disparities and mental disorders. Mental disorders that occur during the Covid-19 pandemic are anxiety, fear, stress, depression, panic, sadness, frustration, anger, and denial. This situation is not only felt by the public, but also experienced by all health workers such as doctors, nurses, midwives. and other health professions. The number of nurse turn overs at Makassar City Hospital from 2019 -2020 was 11 people. This research uses quantitative research methods with a cross sectional research design. Data collection uses a questionnaire. The sample in this study was all 72 inpatient nurses at Makassar City Regional Hospital in 2021. Data analysis using the chi-square test is to see the relationship between the independent variable and the dependent variable. The results of the study showed that there was a significant influence between Environment (P=0.020<α 0.05), Availability of PPE (P=0.013<α 0.05), Family Status (P=0.009<α 0.05), Gender ( P=0.021<α 0.05) and Experience (P=0.007<α 0.05) with nurses' anxiety during the Covid-19 pandemic in the inpatient installation of Makassar City Regional Hospital in 2021. Makassar City Regional Hospital is expected to meet the availability of PPE, especially protective equipment eyes (goggles).